Narrative Analysis of the Conclave (2024) Film - Louisa Christine Hartanto; Patrisia Amanda Pascarina; Imanuel Deni Krisna Aji; Jennifer Laurent; Yemima Elihu Virdiantoro (Pusat Studi Gender Universitas Jember, 2026)
The emergence of a new gender group categorized by the acronym LGBTQ+ in society has caused debate. The expressions they show in everyday life divide the opinions of various parties, one of which is the Catholic Church. This study aims to dissect the narrative in the film